The dreamer - Ryan, Pam Munoz. (Scholastic Press, 2010)
A fictionalized biography of the Nobel Prize-winning Chilean poet Pablo Neruda, who grew up a painfully shy child, ridiculed by his overbearing father, but who became one of the most widely-read poets in the world. Includes author's note about the poet.